Optimization of Substrate Variations in Free Water Surface Constructed Wetlands For Pollutant Removal in The Penjemuran River, Sukarami District - Wardhani, Puteri Kusuma; Putri, Nyimas Septi Rika; Safitri, Tamara Nurilah (Program Pascasarjana Universitas Sriwijaya, 2026)
Penjemuran River is polluted by leachate from the Sukawinatan Landfill, causing a decline in water quality that affects local communities. The river is an important water source for daily activities, especially fisheries, but contamination threatens aquatic life and disrupts livelihoods that rely on it. This study investigated the effect of substrate variations on the efficiency of Free Water Surface (FWS) constructed wetland for pollutants removal. A laboratory scale experiment was conducted using a 60 cm × 30 cm × 50 cm reactor filled with pre-filtered water from the Penjemuran River. The system was tested with three substrates: sand and gravel, biochar, and zeolite, with Wrightia religiosa (water jasmine) as the vegetation. The hydraulic residence time (HRT) was set at 24 hours. The results showed that the biochar was the most effective in removing ammonia (83.2%), while zeolite had the highest removal efficiency for COD by 81.9% and TSS by 75%. Meanwhile, sand and gravel performed best in reducing BOD by 89.4%. The pH remained stable between 6 and 8, meeting Class II water quality standards under Government Regulation 22 of 2021. Based on these findings, a field-scale was designed using a combination of biochar and zeolite to optimize treatment performance. A cost estimate was also calculated to support implementation in the field. This research provides an innovative and sustainable approach to improving water quality, helping to restore aquatic ecosystems and support fisheries.